Rise of the jumbies - Baptiste, Tracey (Algonquin Young Readers, 2017)
Suspicion falls on half-jumbie Corinne when local children from her Caribbean island home begin to disappear, and she is forced to go deep into the ocean to seek the help of a dangerous jumbie who rules the waves.